Neonatal COVID-19 exposures and infections: a systematic review of modes of transmission, manifestations and management - Obumneme B. Ezeanosike; Dorathy C. Obu; Olapeju W. Daniyan; Onyinye U. Anyanwu; Ijeoma N Okedo-Alex; Ifeyinwa C Akamike; Edak Ezeanosike (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background Since the emergence of the novel coronavirus disease (COVID-19) in December 2019, several publications have emerged describing the manifestations of the disease in different age groups. Reports from the newborn group have however been sparse. This review summarizes the mode of transmission, clinical presentations as well as treatment and outcomes of COVID-19 in neonates. # Methods A systematic search for literature was conducted in April and in August 2020. The databases searched include PUBMED, Ovid MEDLINE, EMBASE, CINAHL, Web of Science, and Google Scholar. The search terms used included COVID-19, SARS-CoV-2, Corona virus, Newborn, Neonate, exposure, vertical transmission, breastfeeding, droplet infection. We included primary studies that were carried out globally either in hospitals or in the communities such as case reports, case series, cross-sectional studies and other qualitative or quantitative studies and published in English language, between January and August 2020. # Results Fifty six studies were included in this review. Studies were conducted in China, Iran, South Korea, Peru, USA, Spain, Belgium, France, and Australia. A total of 416 neonates were examined between few hours old and 28 days of age. A total of 38 neonates had PCR-confirmed COVID-19 disease following testing. Fourteen (36.8%) out of the 38 neonates that tested positive had no symptoms. Clinical features reported were mild and include systemic features such as fever (4.1%), respiratory features such as tachypnoea (5.1%), cardiovascular, gastrointestinal, and dermatological features. Radiological features reported include pneumonia (1%), ground glass opacity (2.9%), consolidation (0.7%), increased lung markings (0.3%). Person to person transmission was more common. Treatment was generally supportive. # Conclusions There is little evidence of vertical transmission in neonates. Neonatal survival following COVID-19 infection is very high perhaps due to mild nature of the disease in this age group. More research using higher quality study designs and methodologies is recommended.